Biobanks and the search for predictive biomarkers of local and systemic outcome in atherosclerotic disease - Hurks, Rob; Peeters, Wouter; Derksen, Wouter J. M.; Hellings, Willem E.; Hoefer, Imo E.; Moll, Frans L.; de Kleijn, Dominique P. V.; Pasterkamp, Gerard (Thrombosis and Haemostasis, 2009)
Multiple risk factors have been associated with progression of atherosclerosis. To identify the individual patient who is at risk for disruption of a vulnerable plaque, leading to a cardiovascular event, remains a major challenge. Current screening methods, based on traditional risk factors, do not allow risk stratification on an individual level. The discovery of new biomarkers would aid in identifying specific patient groups at risk for adverse cardiovascular events due to atherosclerotic disease progression. The current definition of the vulnerable plaque, e.g. atheromatous inflammatory plaque with a thin fibrous cap, has been based on cross-sectional post-mortem studies. The predictive value of these histological characteristics of the vulnerable plaque is likely to be low, because they are also frequently observed at multiple locations in symptomatic and asymptomatic patients. The Athero-express study follows a new concept to search for the atherosclerotic patient who may suffer from adverse events. In this study, we investigate the predictive value of local plaque composition for adverse events in other vascular territories, regarding the plaque as a concentrated expression of this systemic disease. First results from this longitudinal biobank study show that the local plaque hides strong predictive value for cardiovascular events elsewhere in the vascular tree. Longitudinal biobank studies will facilitate the identification of novel local plaque markers. The search for the plaque protein signature that is predictive for adverse events might enable patient stratification that will allow individualized tailor made medicine and subsequently guide the choice for therapeutic interventions.
Keywords: Atherosclerosis; biobank; vulnerable plaque; biomarker; plaque signature